Defining Optimal Cut-Points for Cardiorespiratory Fitness Associated With Overweight/Obesity in Children: A School-Based Study - Kasović, Mario; Štefan, Lovro; Petrić, Vilko; Štemberger, Vesna; Blažević, Iva (Frontiers in physiology, 2022)
The main purpose of the study was to define optimal criterion-referenced cut-points for cardiorespiratory fitness (CRF) associated with overweight/obesity. In this cross-sectional study, participants were 1,612 children aged 7-14 years (mean age ± SD = 9.7 ± 2.4 years; 52.5% girls). CRF was assessed by the Maximal multistage 20-m shuttle run test, from which maximal oxygen uptake (VO2max) was estimated. Anthropometric indices included body-mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR). Receiver operating characteristic (ROC) curves were performed to determine cut-off points. In boys, the optimal cut-off points of CRF in defining overweight/obesity for BMI, WC, and WHtR were 44.6, 46.4, and 46.9 mlO2/kg/min. The areas under the curves (AUC) were 0.83 (95% CI 0.78-0.88, p < 0.001), 0.77 (95% CI 0.71-0.83, p < 0.001), and 0.90 (95% CI 0.86-0.93, p < 0.001). In girls, the optimal cut-off points were 41.0, 40.8, and 40.7 mlO2/kg/min for BMI, WC, and WHtR, with the AUCs of 0.86 (95% CI 0.82-0.90, p < 0.001), 0.83 (95% CI 0.79-0.88), and 0.88 (95% CI 0.84-0.93, p < 0.001). In conclusion, our newly developed cut-off points for CRF assessed by the Maximal multistage 20-m shuttle run test may adequately detect primary school-aged boys and girls with general and abdominal obesity.
Keywords: receiver operating curve; diagnostics; anthropometric indices; maximal oxygen uptake; primary-school students